Modernization of policy for food manufacturing and farming may be necessary for global health - Singh R.B.; Sharma J.P.; Takahashi T.; Juneja L.R.; Watson R.R.; Tomar R.S.; Singh M.; Jaglan P.; Singh M.; Halmy E.; Chauhan A.K.; Onsaard E. (My University, 2025)
The major noncommunicable diseases (NCDs)-obesity, type 2 diabetes, cardiovascular disease, cancer, and chronic obstructive pulmonary diseases-are rapidly increasing in almost all countries and are now among the world’s biggest killers. NCDs are polygenic and multifactorial and pose a major challenge to economic development and urbanization being due to increased prosperity of populations with food security across the world. The contributing factors are multifaceted and complex, characterized with food production by farming and food manufacturing by the industry as well as by food prices determined by the governments. Other factors may be extensive advertisements by the food industry and inadequate legislation in labeling food contents. Health behavior related to population aging, urbanization, the globalization of trade and marketing, and the resulting progressive increase in unhealthy patterns of diets and eating also appear to be important. A change in policy aimed at manufacturing only slowly absorbed functional foods to be available at affordable price can increase the consumption of these foods. Plant breeding and genetic engineering should be used to develop new foods as a weapon to reduce the cost of expensive healthy foods such as walnuts and almonds as well as vegetables and fruits. © 2019 Elsevier Inc. All rights reserved.